Falling Kingdoms: Rebel Spring - Book 2 - Rhodes, Morgan (New York, New York : Razorbill, an imprint of Penguin Group (USA), 2013)
When the evil King Gaius announces that a road is to be built into the Forbidden Mountains, formally linking all of Mytica together, he sets off a chain of events that will forever change the face of this land, forcing Cleo the dethroned princess, Magnus the reluctant heir, Lucia the haunted sorceress, and Jonas the desperate rebel to take steps they never could have imagined.
Keywords: Princesses -- Fiction; Fantasy fiction